Exploitation des ressources naturelles et échange écologique inégal : une approche globale de la dette écologique - Boris Schmitt (VertigO)
The point here is to contextualize the problem of ecological debt, to demonstrate that it appears within the framework of a world system characterized by an international division of labour. This international division of labour is particularly determining concerning natural resources exploitation. Some geographic areas remain specialized in raw materials extraction or ecosystem services supply, suffering ecological, economical or social disadvantages, while other areas consume these materials and services and re-inject them into diversified and value adding production processes. Raw materials prices do not rightly reflect the whole of the socio-ecological burdens that extraction processes involve ; neither can they reflect all the economic benefits which can be drawn from the industrial processing of raw materials. Ecological debt emerge from these contradictions. Among the different analysis of the formation of the ecological debts within the world-system, one can find the contribution of the ecological unequal exchange school of thought. The latter has brought to the research effort such original concepts as social metabolism, and precious analytical tools such as core-periphery analysis or methods to assess unequal exchanges of matter and energy. One has to adapt these concepts and methods to the constantly evolving relations of economic power within the world-system, and to avoid predetermined view of things.